1996
DOI: 10.1148/radiology.198.2.8596840
|View full text |Cite
|
Sign up to set email alerts
|

Invasive cervical carcinoma: role of MR imaging in pretreatment work-up--cost minimization and diagnostic efficacy analysis.

Abstract: Guidelines for the pretreatment work-up of clinical stage Ib cervical cancer need revision. MR imaging should be used as an adjunct to clinical evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
7

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(59 citation statements)
references
References 0 publications
0
52
0
7
Order By: Relevance
“…[51][52][53] MRI also has been shown to be a cost-effective staging technique. Hricak et al 54 reported that patients with cervical cancer who underwent MRI as the initial imaging procedure for staging required fewer tests and procedures compared with those who underwent standard clinical staging. The resultant cost savings was significant, not only in terms of the cost of saved procedures but also in terms of the overall cost of treatment when treatment was altered based on MRI findings.…”
Section: Mrimentioning
confidence: 99%
“…[51][52][53] MRI also has been shown to be a cost-effective staging technique. Hricak et al 54 reported that patients with cervical cancer who underwent MRI as the initial imaging procedure for staging required fewer tests and procedures compared with those who underwent standard clinical staging. The resultant cost savings was significant, not only in terms of the cost of saved procedures but also in terms of the overall cost of treatment when treatment was altered based on MRI findings.…”
Section: Mrimentioning
confidence: 99%
“…Clinical palpation is also a subjective method and has significant interobserver variability [26][27][28]. More recent studies have shown that the three-dimensional quantitative imaging-based method of tumor size measurement using MRI is highly accurate in determining actual tumor size and extent to surrounding tissue [2,3,15,16,[29][30][31][32][33][34][35][36][37]. MRI has been recognized as an important imaging modality for the management of cervical cancer because of its multiplanar capability and distinct tissue contrast, particularly between tumor and surrounding normal tissue [9].…”
Section: Discussionmentioning
confidence: 99%
“…This high NPV for bladder invasion suggests that the low pre-test probability of bladder involvement in early stage cervical cancer does not justify routine cystoscopy [7,13]. However, for the positive predictive value (PPV) of MRI for bladder invasion, studies show highly discrepant values ranging from 7% to 100% [6][7][8][9][10].…”
Section: Significance Of Bladder Wall Invasion On Mri In Cervical Cancermentioning
confidence: 99%